(rev.) Raphaël Lefèvre, Ashes of Hama: The Muslim Brotherhood in Syria, Hurst & Company, London 2013, pp. 288 - Malantowicz, Artur (The Copernicus Journal of Political Studies, 2018)
Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14763